2011
DOI: 10.1007/s00418-011-0862-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inflammation on the expression and distribution of the MAS-related gene receptors MrgE and MrgF in the murine ileum

Abstract: The MAS-related gene (Mrg) receptor MrgE has been suggested to be expressed at all tissue levels involved in pain sensation and to influence the expression of another Mrg receptor, MrgF. Given the knowledge on the role of the enteric nervous system (ENS) in sensation, and the plasticity of enteric neurons during intestinal inflammation, it can be hypothesized that MrgE is expressed in enteric neurons, and that MrgE and MrgF change expression in intestinal inflammatory conditions. Therefore, we aimed to reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…In accordance with these findings, transcripts of MRGPRF, formally known as rat thoracic aorta receptor, were detected in small and large intestine (Ross et al, 1990). More precisely, MRGPRE and MRGPRF proteins were detected in both myenteric and submucosal neurons, the latter showing coexpression of both receptors in 30-50% of neurons analyzed (Avula et al, 2011). The same study reported that intestinal schistosomiasis and trinitrobenzene sulfonic acidinduced ileitis resulted in decreased expression of both receptors, whereas other neuronal marker proteins, e.g., calretinin or neuronal nitric oxide synthetase (nNOS), were not affected by either inflammatory insult.…”
Section: Expressionsupporting
confidence: 74%
See 1 more Smart Citation
“…In accordance with these findings, transcripts of MRGPRF, formally known as rat thoracic aorta receptor, were detected in small and large intestine (Ross et al, 1990). More precisely, MRGPRE and MRGPRF proteins were detected in both myenteric and submucosal neurons, the latter showing coexpression of both receptors in 30-50% of neurons analyzed (Avula et al, 2011). The same study reported that intestinal schistosomiasis and trinitrobenzene sulfonic acidinduced ileitis resulted in decreased expression of both receptors, whereas other neuronal marker proteins, e.g., calretinin or neuronal nitric oxide synthetase (nNOS), were not affected by either inflammatory insult.…”
Section: Expressionsupporting
confidence: 74%
“…MRGPRE transcripts were also monitored in medium-and large-diameter neurons of human DRG sections (Zhang et al, 2005) and in other areas of the central nervous system, including cerebral cortex, hippocampus, spinal cord, and cerebellum, as well as in human, mouse, and rat placenta (Zhang et al, 2005;Milasta et al, 2006). MRGPRE and MRGPRF are also expressed in enteric neurons (Avula et al, 2011), belonging to one of the main divisions of the autonomic nervous system that regulates gastrointestinal functions. In accordance with these findings, transcripts of MRGPRF, formally known as rat thoracic aorta receptor, were detected in small and large intestine (Ross et al, 1990).…”
Section: Expressionmentioning
confidence: 99%
“…However, the localization of rMrgprA expression in the vasculature and in the collecting duct of the kidney was recently reported in detail, and an inhibition of vasopressin signaling by rMrgprA was postulated (Kishore et al, 2013). One group has systematically analyzed the expression of all Mrgprs in mouse intestine (Avula et al, 2011(Avula et al, , 2013. With a few exceptions, they are all expressed on different types of enteric neurons in varying levels; however, the function of Mrgprs in these cells is elusive.…”
Section: Expression Of Mas-related G Protein-coupled Receptors In mentioning
confidence: 99%
“…Whole-mounts and cryosections were prepared as described before. 8,9 Tissue samples were preincubated in 0.1 M phosphatebuffered saline (PBS; pH 7.4) with 0.05% thimerosal, 10% normal horse serum, and 1% triton X-100. In case of anti-HuC/D staining this was supplemented with Mouse-On-Mouse blocking reagent (Vector Labs, Burlingame, CA, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%